Pengaruh Pengendalian Akuntansi, Sistem Pelaporan Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Kinerja Instansi Pemerintah - Rio Pratama; Henri Agustin; Salma Taqwa (Universitas Negeri Padang, 2019)
The research aimed to analyze the effect of budget goal clarity, controls accounting and systems reporting for performance accountability of toward government agencies. respondents in this research is the civil servants who served as head of finance , program and evaluation , treasurer and finance staff in 17 SKPD of District Padang Pariaman. The amount of samples in this study was 64 respondents. The sample collection method using a basic formula Yamane, while the method of processing data using multiple linear regression analysis. The partial testing results showed that accounting controls and reporting systems have significant effect on performance accountability of government agencies and simultaneous testing showed significant positive effect on performance accountability of government agencies in Padang Pariaman. The goal budget clarity have no effect on performance accountability of government agencies in Padang Pariaman